(3GdHQb GdeJGdjb aj eMGSf Ldbs - (3eMeO Hf eUWai Hf NOGhjQOi Hf eQGO Hf EHQGgjes; (3GdHdGPQj , CMeO Hf jMji Hf LGHQ Hf OGhO,J (B279 (3g` s ((3eMeO OQhjT Hf jMji Hf eUWai Hf eMeO GdWGdhi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi ZQS OhGe GdJhMjO haLQ ajgG jfGHjY GdMceI eSJeO ef ajV Pi GdMceg s
(3BNQgG (B:s
(3eMGSf GdTGe fGOJ aGdZOjOI hMOi h cd MSf dZjQi aGfeG gh HYOi hgPG BNQ eG SQOI s
(3GfXQ GdChd ef GdJGQjN Qbe (B83s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B201s
Keywords: (3GdJGQjNs